(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides an ecological assessment of man-made soil pollution in the urbanized areas of the Fergana Valley, and compares the man-made soil pollution in the landscape, especially due to the influence of industry and transport, the normative indicators of some heavy metals that may be in the soil, and their relative amounts compared to the permissible norm (REM).